(untitled) (Global Journal of Medical Research, 2011)
Abstracts -Liver glycogen content and liver glycogen synthesis are lowered in diabetes mellitus due to lack of functioning insulin. Many enzymes of glycogen metabolism as well as glucose metabolism are sulfhydryl in nature and are affected by changes in cellular thiol-disulfide ratio. Certain low molecular weight thiols can influence glucose uptake and utilization in fat cells and in muscle cells. A study was undertaken to establish the effect of thiopropanol ( 3-mercapto 1 propanol) on glycogen breakdown in isolated alloxan diabetic liver. The results indicate that thiopropanol influences glycogen breakdown, lactic acid production in alloxan diabetic liver which may be attributed to increased activity of hexokinase in thiopropanol-exposed-alloxan diabetic liver